Analisis Pengendalian Bahan Baku Jasa Maklon dengan Menggunakan Metode Eoq (Economic Order Quality) Berbasis Big Data Logistik Guna Meminimalisir Biaya Produksi pada PT Barata Indonesia (Persero) - Dina Eka Shofiana; Dwi Novita Sari (Majalah Ilmiah Bijak, 2018)
This study aims to determine the control of raw materials by using EOQ (Economic Order Quality) method to minimize production costs in PT Barata Indonesia (Persero). This research uses Adeskriptif with qualitative approach.The results of this study indicate that the control of raw materials using the EOQ (Economic Order Quallity) method can minimize production costs in PT Barata Indonesia (Persero) as follows: Silica Sand raw material can minimize production cost of Rp 16,321,500. Fero Silicon minimize the production cost of Rp 7,520,550,000, the raw material of Fero Mangan Mc can minimize the cost of Rp 2,255,625,000, the raw material of Fero Mangan Hc can minimize the cost of Rp 1.098,600. the raw material of Scrap can minimize the cost of Rp 324,995,000.